2016
DOI: 10.17159/sajs.2016/2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Investigating atmospheric photochemistry in the Johannesburg-Pretoria megacity using a box model

Abstract: Urban air pollution has become a major concern over the past decades. One of the largest conurbations in Sub-Saharan Africa is developed around the cities of Johannesburg and Pretoria (Jhb-Pta megacity). In this study, a photochemical box model with a detailed representation of ozone (O 3 ) formation chemistry was used to investigate the state of current air quality and photochemical processes in the Jhb-Pta megacity, as well as scenarios that could possibly mitigate air pollution. Results indicated that the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The area in which Elandsfontein is situated is a well-known international NO 2 hotspot, with tropospheric column densities similar to what is observed over southeast Asia (Lourens et al, 2012(Lourens et al, , 2016. It is widely accepted that NO 2 in this hotspot mainly originates from NO x emission from coal-fired power stations.…”
Section: Diurnal Variationsmentioning
confidence: 85%
“…The area in which Elandsfontein is situated is a well-known international NO 2 hotspot, with tropospheric column densities similar to what is observed over southeast Asia (Lourens et al, 2012(Lourens et al, , 2016. It is widely accepted that NO 2 in this hotspot mainly originates from NO x emission from coal-fired power stations.…”
Section: Diurnal Variationsmentioning
confidence: 85%
“…Anthropogenic sources of VOCs are largely due to industrial and vehicular emissions (Jaars et al, 2014), while biogenic VOCs are also naturally emitted (Jaars et al, 2016). Regional biomass burning, which includes household combustion for space heating and cooking, agricultural waste burning, and open biomass burning (wild fires), is a significant source of CO, NO x , and VOCs (Macdonald et al, 2011;Crutzen and Andreae, 1990;Galanter et al, 2000;Simpson et al, 2011) in southern Africa. In addition, stratospheric intrusions of O 3 -rich air to the free troposphere can also lead to elevated tropospheric O 3 concentrations (Diab et al, 1996(Diab et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Under VOC-limited conditions, O 3 concentrations increase with increasing VOCs, while a region is considered NO x limited when O 3 production increases with increasing NO x concentrations. Results from a photochemical box model study in South Africa, for instance, revealed that the Johannesburg-Pretoria megacity is within a VOC-limited regime ( Lourens et al, 2016 ). VOC reductions would, therefore, be most effective in reducing O 3 , while NO x controls without VOC controls may lead to O 3 increases.…”
Section: Introductionmentioning
confidence: 99%
“…In order for South Africa to develop an effective national/provincial management plan to reduce O3 concentrations through controlling NOx and VOC emissions, it is important to determine whether a region is NOx-or VOC-limited. Results from a photochemical box model study in South Africa, for instance, revealed that the Johannesburg-Pretoria megacity is within a VOC-limited regime (Lourens et al, 2016). 5…”
mentioning
confidence: 99%